CHARACTERIZATION OF PASTA WITH THE ADDITION OF CICER ARIETINUM AND SALVIA HISPANICA FLOURS ON QUALITY AND ANTIOXIDANT PARAMETERS - COTA-GASTÉLUM, A.G.; SALAZAR-GARCÍA, MG.; ESPINOZA-LÓPEZ, A.; PEREZ-PEREZ, L.M.; CINCO-MOROYOQUI, F.J.; MARTÍNEZ-CRUZ, O.; WONG-CORRAL, F.J.; DEL-TORO-SÁNCHEZ, C.L. (Italian Journal of Food Science, 2019)
Quality parameters, antioxidant properties, in vitro digestion and consumer acceptance were determined in pasta prepared with chickpea and chia flours. Pastas fortified with chia and chickpea increased protein, fiber content, total phenols, and antioxidant capacity with respect to the control. More than 85% of the antioxidant capacity and over 90% of the phenolic compounds in cooked pasta were retained after in vitro digestion, which is considered high. Pasta prepared with 25% wheat semolina, 10% chia flour, and 65% chickpea flour has high quality parameters, phenol content, antioxidant capacity and consumer acceptance.